2010
DOI: 10.4238/vol9-1gmr689
|View full text |Cite
|
Sign up to set email alerts
|

Association of lipase lipoprotein polymorphisms with high-density lipoprotein and triglycerides in elderly men

Abstract: ABSTRACT. Lipoprotein lipase is essential for triglyceride hydrolysis. The polymorphisms S447X in exon 9 and HindIII in intron 8 have been associated with lower triglyceride levels and lower cardiovascular risk in adult men. We examined the association of these lipoprotein lipase polymorphisms with high-density lipoprotein (HDL) and triglyceride levels in elderly men. Blood samples were obtained from 87 elderly men, 48 of whom had cardiovascular disease and 39 (controls) had no history of cardiovascular events… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Amer et al [28] have also reported a significant increase in plasma levels of TG and significant decrease in HDL in CAD patients bearing HindIII (++) genotype. However, on contrary Araujo et al [29] reported an association of HindIII polymorphism with lower TG levels and cardiovascular risk in elderly men. HDL concentrations and the extent of coronary heart diseases have been reported to be inversely related because HDL particles play a crucial role in reverse cholesterol transport [14,15,30].…”
Section: Discussionmentioning
confidence: 92%
“…Amer et al [28] have also reported a significant increase in plasma levels of TG and significant decrease in HDL in CAD patients bearing HindIII (++) genotype. However, on contrary Araujo et al [29] reported an association of HindIII polymorphism with lower TG levels and cardiovascular risk in elderly men. HDL concentrations and the extent of coronary heart diseases have been reported to be inversely related because HDL particles play a crucial role in reverse cholesterol transport [14,15,30].…”
Section: Discussionmentioning
confidence: 92%
“…Similar results, like LPL H + H + genotype, was a risk factor for myocardial infarction in Brazil and Russian population 65 and significantly associated with myocardial infarction (MI) patients in South Indian population 66 , but these polymorphic studies are very limited in India. In another study observed H¯ (G) allele was not associated with blood lipids or cardiovascular events 67 and also a recent study conducted by Marcia et al reported H + /H + (T/T) genotype and the H + (T) allele were associated with elevated VLDLc and triglycerides levels (P < 0.05) and reduced HDL-C levels (P < 0.05) 68 . Likewise, H¯ H¯ (G/G), H + H¯ (T/G) and H + H + (T/T) genotypes of intron 8 T >G LPL gene no significant differences in the serum levels of TC, TG, HDL-c and LDL-c in Saudi Population 69 similarly a study between the control and coronary artery disease in Shiraz City observed, this polymorphism doesn't have any significant association with CAD 70 .…”
Section: Atherogenic Ratios Like Castelli's Risk Index-i (Cri-i)mentioning
confidence: 85%
“…As regards the HindIII polymorphism, the presence of the mutant H-allele did not show any influence on the levels of the different parameters of the lipid profile. Such findings proved that the location of HindIII polymorphism in the middle of intron 8 makes it a non functional polymorphism with almost negligible direct effect on LPL activity (Antonio et al, 2013;Araújo et al, 2010;Chen et al, 2008). gene variants which they consider the main contributors to the change in LPL activity.…”
Section: Table (1)mentioning
confidence: 92%